2019
DOI: 10.3390/biomimetics4030058
|View full text |Cite
|
Sign up to set email alerts
|

Evo-Devo Algorithms: Gene-Regulation for Digital Architecture

Abstract: The majority of current visual-algorithmic architecture is constricted to specific parameters that are gradient related, keeping their parts’ relation fixed within the algorithm, far away from a truly parametric modeling with a flexible topology. Recent findings around genetics and certain genes capable of shape conditioning (development) have succeeded in recovering the science of embryology as a valid field that connects and affects the evolutionary ecosystem, showing the existence of universal mechanisms th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Evo-devo provides a number of developmental steps for fine-tuning an organism, but in the algorithmic world this is unnecessary when more generations can be run instead. It is possible to apply evo-devo specific applications, such as digital architectures [ 70 ], where domain-specific concepts in architecture can be linked to evo-devo processes, and the time required to generate solutions makes fewer generations more suitable. The design of neural networks using GA [ 71 ] mimics evo-devo concepts with limited success as neural networks already learn through their training process, and evolutionary algorithms are typically used to network parameters such as weights and architecture [ 72 ].…”
Section: Missing Concepts From the Extended Evolutionary Synthesismentioning
confidence: 99%
“…Evo-devo provides a number of developmental steps for fine-tuning an organism, but in the algorithmic world this is unnecessary when more generations can be run instead. It is possible to apply evo-devo specific applications, such as digital architectures [ 70 ], where domain-specific concepts in architecture can be linked to evo-devo processes, and the time required to generate solutions makes fewer generations more suitable. The design of neural networks using GA [ 71 ] mimics evo-devo concepts with limited success as neural networks already learn through their training process, and evolutionary algorithms are typically used to network parameters such as weights and architecture [ 72 ].…”
Section: Missing Concepts From the Extended Evolutionary Synthesismentioning
confidence: 99%
“…Evo-devo provides a number of developmental steps for fine tuning an organism, but in the algorithmic world this is unnecessary when more generations can be run instead. It is possible to apply evo-devo specific applications, such as digital architectures [73], where domainspecific concepts in architecture can be linked to evo-devo processes, and the time taken to generate solutions means a lower number of generations can be run. Similarly, genomic evolution involves the evolution of genome architecture itself.…”
Section: Missing Concepts From the Extended Evolutionary Synthesismentioning
confidence: 99%
“…Previous research studies have shown the functionality of 3D polygon meshes to mimic biological body plan structures [32]: patterns, Boolean operations, subdivision, orientation, symmetry, and polarity. The very same structures observed in embryology are often used in 3D modeling software.…”
Section: Emergence Patterns and Colourimetrymentioning
confidence: 99%
“…As has been previously stated by the authors [32], meshes excel at applying different modifications in a universal way, and allow a new toolkit of genes to be introduced that alters the topology of the case at hand (Figure 8). Depending on the scale or step, these modifications can produce massive changes or can become superficial adaptations.…”
Section: Homeotic Genes As Topology-dependent Mesh Modifiersmentioning
confidence: 99%